Pharmacokinetically-guided dosing of pemetrexed in a patient with renal impairment and a patient requiring hemodialysis. (April 2019) - de Rouw, N.; Croes, S.; Posthuma, R.; Agterhuis, D.E.; Schoenmaekers, J.J.A.O.; Derijks, H.J; Burger, D.M.; Dingemans, A.M.; ter Heine, R.
Highlights: Renal impairment is highly prevalent in lung cancer patients. Pemetrexed is currently contraindicated in patients with creatinine clearance <45 mL/min. Pharmacokinetically-guided dosing of pemetrexed seems a feasible treatment strategy for these patients. Abstract: Objectives: Pemetrexed is indicated for non-small cell lung cancer and mesothelioma. Dosing is based on body surface are (BSA), while renal function is the only determinant for exposure and thus toxicity. BSA-based dosing introduces large variability in exposure and may lead to (hemato)toxicity in patients with impaired renal function. Therefore, pemetrexed is contraindicated in renal impairment. The presented cases provide proof-of-concept for pharmacokinetically-guided dosing of pemetrexed in a haemodialysis patient and a patient with mild renal impairment. Methods: The pharmacokinetic target was an area under the concentration-time curve (AUC) of 123–205 mg·h/L. Using a previously developed population pharmacokinetic model, individual pharmacokinetics were estimated. Results: Both patients had an exposure above target after the initial dose, but a proportional dose reduction resulted in a therapeutic exposure in both patients (185 and 166 mg·h/L, respectively), that was well-tolerated. Interestingly, a threefold increase in systemic clearance of pemetrexed was observed during hemodialysis (from 1.00 L/h to 3.01 L/h), which approximates the population clearance of pemetrexed. Conclusion: Altogether, we showed that pharmacokinetically-guided dosing of pemetrexed may be a feasible strategy for patients with lung cancer and renal impairment.